A high tensile PA6-based hydrogel composite material and preparation method thereof

By introducing PA6 and liquid polyisoprene into the hydrogel and adopting a specific solution preparation and drying process, a high-stretch PA6-based hydrogel composite is prepared, which solves the problem of insufficient mechanical properties of traditional hydrogels, and achieves high tensile performance and excellent mechanical properties, which is suitable for high-end applications.

CN119019841BActive Publication Date: 2025-04-22JIANGSU HENGLI CHEM FIBER
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411524677.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-04-22
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

The mechanical properties of traditional hydrogels are poor, limiting their applications in high-end fields such as flexible electronics, wearable devices, etc.

Method used

Using the preparation method of high-stretch PA6-based hydrogel composite, an aqueous solution containing PA6, polyvinyl alcohol, polyacrylamide, pectin, formic acid and water, and an oil-phase solution containing liquid polyisoprene, benzyl alcohol and cyclohexyl methacrylate, were prepared, and then mixed at high temperature, to form a highly stretched PA6-based hydrogel composite.

Benefits of technology

The high tensile properties and excellent mechanical properties of the hydrogel are achieved, with an elongation of break of 2629~2870%, a tensile strength of 3.8~4.2MPa, an elastic modulus of 1.01~1.36kPa, and a shorter time, no need for crosslinking agents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119019841B_ABST
    Figure CN119019841B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of polymer materials, and relates to a high-stretch PA6-based hydrogel composite material and a preparation method thereof. After preparing an aqueous phase solution containing PA6, polyvinyl alcohol, polyacrylamide, pectin, formic acid and water and an oil phase solution containing liquid polyisoprene, benzyl alcohol and cyclohexyl methacrylate, the aqueous phase solution and the oil phase solution are mixed at 100-110°C for 30-40 minutes, and then freeze-dried to obtain a high-stretch PA6-based hydrogel composite material. The present invention introduces PA6 into the preparation of the hydrogel composite material, realizes the reuse of waste resources, conforms to the concept of sustainable development, and the preparation process is short in time. The obtained high-stretch PA6-based hydrogel composite material has excellent mechanical properties and elasticity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials and relates to a high-stretch PA6-based hydrogel composite material and a preparation method thereof. Background Art

[0002] As a three-dimensional polymer material formed by physical or chemical cross-linking, hydrogel has shown broad application prospects in many fields due to its unique hydrophilicity and three-dimensional network structure. According to the source of ingredients, hydrogels are mainly divided into two categories: natural hydrogels and synthetic hydrogels. Natural hydrogels, such as polysaccharides and polypeptides, are favored in the biomedical field for their good biocompatibility and degradability. Synthetic hydrogels are made by chemical cross-linking of polymer compounds such as alcohols and acrylic acid, and have more flexible design and controllability.

[0003] There are various ways to crosslink hydrogels, including physical crosslinking and chemical crosslinking. Physical crosslinking is achieved through intermolecular forces such as hydrogen bonds and electrostatics, while chemical crosslinking builds a stable three-dimensional network through the formation of chemical bonds. These properties give hydrogels excellent water absorption and retention capacity, biocompatibility and stimulus responsiveness, making them have important application value in cosmetics, biosensors, tissue engineering and other fields.

[0004] However, traditional hydrogels have poor mechanical properties, which to some extent limits their application in high-end fields such as flexible electronics and wearable devices.

[0005] In order to solve the above problems, patent application CN105175755A discloses a high-strength high-strength double-network physical cross-linked hydrogel and its preparation method, which uses clay as a template, combines acrylic monomers and initiators to prepare high-strength high-strength hydrogels, although the mechanical properties of the hydrogel are improved, but it takes a long time. Patent application CN117843995A discloses a high-strength bondable sodium alginate / polyacrylamide / tannic acid hydrogel and its preparation method and application, which adds sodium alginate, acrylamide and tannic acid to glycerol / water solution, stirs at room temperature to a transparent solution, then adds a cross-linking agent and an initiator to the precursor solution, stirs and dissolves at room temperature, adds calcium chloride solution and stirs evenly, and finally injects the mixture solution into a mold for cross-linking reaction. After the reaction is completed, the hydrogel is placed at room temperature for a period of time to obtain a hydrogel with excellent tensile properties, however, the elasticity of the hydrogel is poor.

[0006] PA6 (polyamide 6, also known as nylon 6) is a high molecular polymer formed by the ring-opening polymerization of ε-caprolactam. It was originally widely used in the form of fibers. PA6 has excellent elasticity and mechanical properties, and its macromolecular chain is rich in repeated amide bonds. As the use of PA6 increases year by year, the amount of waste also increases. If PA6 can be introduced into the preparation of hydrogels, it will not only be conducive to the reuse of waste resources, but also expected to improve the mechanical properties and elasticity of hydrogels, which is in line with the concept of sustainable development. However, there is currently no mature technology for using PA6 to prepare reinforced hydrogels. Summary of the invention

[0007] The purpose of the present invention is to solve the problems existing in the prior art and to provide a high-stretch PA6-based hydrogel composite material and a preparation method thereof.

[0008] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0009] A method for preparing a high-stretch PA6-based hydrogel composite material comprises the following steps: preparing an aqueous solution containing PA6, polyvinyl alcohol, polyacrylamide, pectin, formic acid and water and an oil solution containing liquid polyisoprene, benzyl alcohol and cyclohexyl methacrylate, mixing the aqueous solution and the oil solution at 100-110° C. for 30-40 minutes, and freeze-drying the mixture to obtain the high-stretch PA6-based hydrogel composite material.

[0010] Liquid polyisoprene is called liquid rubber. It is a low molecular weight liquid polymer polymerized with isoprene as a monomer. It can be used as a plasticizer. It is used as a source of hydrogel material in the hope of obtaining better mechanical properties. Since liquid polyisoprene is very stable in most organic reagents and water, it cannot be combined with other materials in the state of a single molecular chain. Therefore, the present invention uses benzyl alcohol, which has a solubility parameter close to that of liquid polyisoprene. In the three principles of polymer solubility, polymers with similar solubility often have good compatibility, but they can also be affected by factors such as solvation and become insoluble in practice. Therefore, although benzyl alcohol cannot dissolve liquid polyisoprene, it can swell it, increase the space between molecular chains, and provide a channel for substances to enter and exit.

[0011] In the oil phase solution, benzyl alcohol has good compatibility with liquid polyisoprene, and the binding force between the two is recorded as F1; in the aqueous phase solution, polyvinyl alcohol has good compatibility with other water-soluble substances such as PA6, and the binding force between the two is recorded as F3; in the process of mixing the aqueous phase solution and the oil phase solution, the aqueous phase solution can be dispersed in the oil phase solution in the form of droplets, so that the benzene ring of benzyl alcohol and the vinyl group of polyvinyl alcohol are combined by van der Waals force, and the binding force between the two is recorded as F2; ​​since liquid polyisoprene has provided a channel for the entry and exit of substances, and F1>F2>F3, liquid polyisoprene Benzyl alcohol attracts benzyl alcohol, benzyl alcohol attracts polyvinyl alcohol, and polyvinyl alcohol attracts other water-soluble substances such as PA6 into the molecular chains of liquid polyisoprene; after the water-soluble substances enter the molecular chains of liquid polyisoprene, on the one hand, the molecular chains of the water-soluble substances will be entangled with the molecular chains of liquid polyisoprene, forming a strong intermolecular force, thereby increasing the mechanical properties of the hydrogel; on the other hand, after PA6 enters the molecular chains of liquid polyisoprene, due to the change in the solvent system, PA6 will be precipitated first, forming an effect similar to that of fiber-reinforced materials, thereby further increasing the mechanical properties of the hydrogel.

[0012] Pectin and PA6 cannot be dissolved in water, and when the methoxy content of pectin is greater than 7, it belongs to high-ester pectin and needs to be acid-lyzed to become water-soluble pectin. PA6 has good chemical inertness and is not only insoluble in water, but also insoluble in most organic reagents. It is only soluble in solvents such as formic acid, meta-cresol, and trifluoroacetic acid at room temperature. Therefore, the present invention uses formic acid aqueous solution as the solvent of the aqueous phase solution. On the one hand, it is to dissolve PA6 at high temperature, and on the other hand, it can change the pH value to acidic conditions to hydrolyze pectin into water-soluble pectin; after the water-soluble pectin is compounded with liquid polyisoprene, the water-soluble substance can be formed; after the introduction of polyacrylamide, the water-soluble pectin can form a strong hydrogen bond with the polyacrylamide. After freeze-drying, the strong hydrogen bond between the two can make the water-soluble substance easy to form, and then buried in the liquid polyisoprene, intertwined and compounded with the liquid polyisoprene, so that the gel is further accelerated and reinforced.

[0013] Cyclohexyl methacrylate can enhance the degree of binding between the molecular chains of liquid polyisoprene and water-soluble substances, making the two more tightly bound, because its ester group and non-polar group have a certain force with liquid polyisoprene, pectin, polyacrylamide, and polyvinyl alcohol. During the mixing process, it can enhance the entanglement degree of the molecular chains of liquid polyisoprene and water-soluble substances.

[0014] As the preferred technical solution:

[0015] In the method for preparing a high-stretch PA6-based hydrogel composite material as described above, the mass ratio of polyvinyl alcohol to PA6 is 4~5:0.05~0.1.

[0016] In the method for preparing a high-stretch PA6-based hydrogel composite material as described above, the mass ratio of polyacrylamide to PA6 is 4~5:0.05~0.1.

[0017] In the method for preparing a high-stretch PA6-based hydrogel composite material as described above, the mass ratio of pectin to PA6 is 3:0.05~0.1, and the mass ratio of water, PA6, and formic acid is 94:0.1~0.2:0.5~0.8.

[0018] In the method for preparing a high-stretch PA6-based hydrogel composite material as described above, the mass ratio of liquid polyisoprene to benzyl alcohol is 1:30~35.

[0019] In the method for preparing a high-stretch PA6-based hydrogel composite material as described above, the mass ratio of liquid polyisoprene to cyclohexyl methacrylate is 8-9:1.

[0020] In the method for preparing a high-stretch PA6-based hydrogel composite material as described above, the mass ratio of the oil phase solution to the water phase solution is 4~5:5.

[0021] In the preparation method of the high-stretch PA6-based hydrogel composite material as described above, the freeze-drying process is: first freezing at a temperature of -70°C, and then freeze-drying for 48 to 50 hours under a vacuum degree of 2Pa.

[0022] The present invention also provides a high-stretch PA6-based hydrogel composite material prepared by the preparation method of a high-stretch PA6-based hydrogel composite material as described in any of the above items. The high-stretch PA6-based hydrogel composite material has an elongation at break of 2629~2870%, a tensile strength of 3.8~4.2MPa, and an elastic modulus of 1.01~1.36kPa.

[0023] Beneficial effects:

[0024] (1) Compared with patent application CN105175755A, the present invention directly uses polymerized polymers (PA6, polyvinyl alcohol, liquid polyisoprene), uses benzyl alcohol to swell the liquid polyisoprene, thereby opening the space between its molecular chains and providing channels for the entry of other polymers, and uses the good compatibility between benzyl alcohol and polyvinyl alcohol, as well as the binding force between polyvinyl alcohol and water-soluble substances such as PA6, to guide these polymer molecular chains into the molecular chains of liquid polyisoprene, so that the molecular chains of each component polymer are naturally entangled and formed, eliminating the polymerization time and taking less time.

[0025] (2) Compared with patent application CN117843995A, the present invention does not require the use of a cross-linking agent. By virtue of the strong interaction force naturally formed between the polymer molecular chains of each component, the hydrogel composite material is endowed with excellent mechanical properties and elasticity.

[0026] (3) The present invention introduces PA6 into the preparation of hydrogel composite materials, realizes the recycling of waste resources, conforms to the concept of sustainable development, and broadens the application of hydrogel in high-end fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a SEM image of the high-stretch PA6-based hydrogel composite material of Example 1 of the present invention. DETAILED DESCRIPTION

[0028] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0029] The testing methods of the relevant performance indicators in the following embodiments and comparative examples are as follows:

[0030] Elongation at break, tensile strength, and elastic modulus: The hydrogel composite material was cut into rectangular samples of 40×10×2 mm (length×width×height) and measured using an MTS Exceed E43 series electronic universal testing machine. The load-strain curve during the stretching process was recorded and analyzed to calculate the elongation at break (i.e., the ratio of the elongation at break to the original length), tensile strength (maximum load divided by the original cross-sectional area), and elastic modulus (obtained by calculating the slope of the linear region of the stress-strain curve in the strain range of 5%-10%) of the hydrogel composite material; wherein the stretching speed was 100 mm / min and the preload was 0.01 N.

[0031] Example 1

[0032] A method for preparing a high-stretch PA6-based hydrogel composite material, the specific steps are as follows:

[0033] (1) Preparation of raw materials;

[0034] Pectin: CAS number is 9000-69-5;

[0035] water;

[0036] Hydrochloric acid solution: concentration is 0.05mol / L, the solvent is water;

[0037] Polyacrylamide: The manufacturer is Henan Zhengjie Environmental Protection Technology Co., Ltd., with a cationic ion degree of 20~55% and a molecular weight of 8~12 million;

[0038] Polyvinyl alcohol: CAS number is 9002-89-5;

[0039] PA6: CAS number is 25038-54-4;

[0040] Formic acid;

[0041] Liquid polyisoprene: manufacturer is Jinan Xiangfa Chemical Technology Co., Ltd., model is LIR-50K;

[0042] Cyclohexyl methacrylate;

[0043] Benzyl alcohol;

[0044] (2) preparing aqueous phase solution and oil phase solution;

[0045] The preparation process of the aqueous phase solution is as follows: first, pectin is uniformly dispersed in water to obtain a pectin dispersion, a hydrochloric acid solution is used to adjust the pH value of the pectin dispersion to 1, and then the pectin dispersion with the adjusted pH value is heated and stirred at 85° C. for 60 minutes, polyacrylamide, polyvinyl alcohol, PA6, and formic acid are added thereto and mixed evenly, and then heated at 95° C. for 40 minutes to obtain an aqueous phase solution; wherein the mass ratio of polyacrylamide to PA6 is 5:0.1, the mass ratio of polyvinyl alcohol to PA6 is 5:0.1, the mass ratio of pectin to PA6 is 3:0.1, and the mass ratio of water, PA6, and formic acid is 94:0.2:0.8;

[0046] The preparation process of the oil phase solution is as follows: liquid polyisoprene and cyclohexyl methacrylate are dissolved in benzyl alcohol to obtain the oil phase solution; wherein the mass ratio of the liquid polyisoprene to the benzyl alcohol is 1:35, and the mass ratio of the liquid polyisoprene to the cyclohexyl methacrylate is 8:1;

[0047] (3) Preparation of high tensile PA6-based hydrogel composites;

[0048] The oil phase solution and the water phase solution with a mass ratio of 4:5 were mixed at 100°C for 30 minutes, first frozen at -70°C, and then freeze-dried at a vacuum degree of 2Pa for 48 hours to obtain a high-stretch PA6-based hydrogel composite material.

[0049] The SEM images of the high tensile PA6-based hydrogel composite material were as follows: Figure 1 As shown; the elongation at break of the high tensile PA6-based hydrogel composite material is 2870%, the tensile strength is 4.2MPa, and the elastic modulus is 1.36kPa.

[0050] Comparative Example 1

[0051] A method for preparing a PA6-based hydrogel composite material is basically the same as that in Example 1, except that pectin and polyacrylamide are not added when preparing the aqueous phase solution; and cyclohexyl methacrylate is not added when preparing the oil phase solution.

[0052] It cannot be formed after freeze-drying. This is because in the absence of pectin and polyacrylamide, the strong hydrogen bond between the water-soluble pectin and the polyacrylamide cannot be formed, making it difficult for the water-soluble substance to be formed and unable to be buried in the liquid polyisoprene to intertwine and compound with the liquid polyisoprene; at the same time, in the absence of cyclohexyl methacrylate, the degree of bonding between the molecular chains of the liquid polyisoprene and the water-soluble substance is insufficient, the two cannot be tightly combined, the degree of entanglement of the molecular chains is insufficient, and the gel structure cannot be further strengthened, which ultimately leads to the inability to form after freeze-drying.

[0053] Comparative Example 2

[0054] A method for preparing a PA6-based hydrogel composite material is basically the same as that in Example 1, except that pectin is not added when preparing the aqueous phase solution.

[0055] The final PA6-based hydrogel composite material had an elongation at break of 230%, a tensile strength of 0.24 MPa, and an elastic modulus of 0.3 kPa.

[0056] Compared with Example 1, the mechanical properties and elasticity of the PA6-based hydrogel composite material in Comparative Example 2 are significantly deteriorated. This is because in Comparative Example 2, since pectin is not added, the strong hydrogen bond between the water-soluble pectin and the polyacrylamide cannot be formed, making it difficult to form the water-soluble substance and difficult to effectively bury it in the liquid polyisoprene to intertwine and composite with the liquid polyisoprene. At the same time, the force formed by the liquid polyisoprene and the polyacrylamide is not strong, so that the gel is not firm after forming, and the mechanical properties and elasticity are deteriorated.

[0057] Comparative Example 3

[0058] A method for preparing a PA6-based hydrogel composite material is basically the same as that in Example 1, except that no polyacrylamide is added when preparing the aqueous phase solution.

[0059] The final PA6-based hydrogel composite material has an elongation at break of 1200%, a tensile strength of 2.1 MPa, and an elastic modulus of 0.7 kPa.

[0060] Compared with Example 1, the mechanical properties and elasticity of the PA6-based hydrogel composite material are significantly deteriorated in Comparative Example 3. This is because in the absence of polyacrylamide, it is impossible to form a strong hydrogen bond with the water-soluble pectin, making it difficult to form the water-soluble substance and difficult to effectively bury it in the liquid polyisoprene to intertwine and compound with the liquid polyisoprene, resulting in the gel being not firm after forming, and the mechanical properties and elasticity being deteriorated.

[0061] Comparative Example 4

[0062] A method for preparing a PA6-based hydrogel composite material is basically the same as that in Example 1, except that cyclohexyl methacrylate is not added when preparing the oil phase solution.

[0063] The final PA6-based hydrogel composite material had an elongation at break of 1800%, a tensile strength of 2.7 MPa, and an elastic modulus of 0.93 kPa.

[0064] Compared with Example 1, the mechanical properties and elasticity of the PA6-based hydrogel composite material in Comparative Example 4 are significantly deteriorated. This is because cyclohexyl methacrylate is not added when preparing the oil phase solution in Comparative Example 4, which weakens the molecular chain bonding degree between the liquid polyisoprene and the water-soluble substance. Due to the lack of the ester group and non-polar group of cyclohexyl methacrylate, it is impossible to generate a certain force with the liquid polyisoprene, pectin, polyacrylamide, and polyvinyl alcohol, so that the entanglement degree of the molecular chain of the liquid polyisoprene and the water-soluble substance cannot be effectively increased during the mixing process, resulting in the weakening of the molecular chain interaction of the PA6-based hydrogel composite material finally obtained, and then the elongation at break, tensile strength and elastic modulus of the material are significantly reduced.

[0065] Example 2

[0066] A method for preparing a high-stretch PA6-based hydrogel composite material, the specific steps are as follows:

[0067] (1) Preparation of raw materials;

[0068] Pectin: CAS number is 9000-69-5;

[0069] water;

[0070] Hydrochloric acid solution: concentration is 0.06mol / L, solvent is water;

[0071] Polyacrylamide: The manufacturer is Henan Zhengjie Environmental Protection Technology Co., Ltd., with a cationic ion degree of 20~55% and a molecular weight of 8~12 million;

[0072] Polyvinyl alcohol: CAS number is 9002-89-5;

[0073] PA6: CAS number is 25038-54-4;

[0074] Formic acid;

[0075] Liquid polyisoprene: manufacturer is Jinan Xiangfa Chemical Technology Co., Ltd., model is LIR-30K;

[0076] Cyclohexyl methacrylate;

[0077] Benzyl alcohol;

[0078] (2) preparing aqueous phase solution and oil phase solution;

[0079] The preparation process of the aqueous phase solution is as follows: first, pectin is uniformly dispersed in water to obtain a pectin dispersion, a hydrochloric acid solution is used to adjust the pH value of the pectin dispersion to 1, and then the pectin dispersion with the adjusted pH value is heated and stirred at 85° C. for 60 minutes, polyacrylamide, polyvinyl alcohol, PA6, and formic acid are added thereto and mixed evenly, and then heated at 95° C. for 30 minutes to obtain an aqueous phase solution; wherein the mass ratio of polyacrylamide to PA6 is 4:0.05, the mass ratio of polyvinyl alcohol to PA6 is 4:0.05, the mass ratio of pectin to PA6 is 3:0.05, and the mass ratio of water, PA6, and formic acid is 94:0.1:0.5;

[0080] The preparation process of the oil phase solution is as follows: liquid polyisoprene and cyclohexyl methacrylate are dissolved in benzyl alcohol to obtain the oil phase solution; wherein the mass ratio of the liquid polyisoprene to the benzyl alcohol is 1:30, and the mass ratio of the liquid polyisoprene to the cyclohexyl methacrylate is 9:1;

[0081] (3) Preparation of high tensile PA6-based hydrogel composites;

[0082] The oil phase solution and the water phase solution with a mass ratio of 5:5 were mixed at 110°C for 40 minutes, first frozen at -70°C, and then freeze-dried at a vacuum degree of 2Pa for 50 hours to obtain a high-stretch PA6-based hydrogel composite material.

[0083] The final high-tensile PA6-based hydrogel composite material has an elongation at break of 2629%, a tensile strength of 3.8 MPa, and an elastic modulus of 1.01 kPa.

[0084] Example 3

[0085] A method for preparing a high-stretch PA6-based hydrogel composite material, the specific steps are as follows:

[0086] (1) Preparation of raw materials;

[0087] Pectin: CAS number is 9000-69-5;

[0088] water;

[0089] Hydrochloric acid solution: concentration is 0.055 mol / L, the solvent is water;

[0090] Polyacrylamide: The manufacturer is Henan Zhengjie Environmental Protection Technology Co., Ltd., with a cationic ion degree of 20~55% and a molecular weight of 8~12 million;

[0091] Polyvinyl alcohol: CAS number is 9002-89-5;

[0092] PA6: CAS number is 25038-54-4;

[0093] Formic acid;

[0094] Liquid polyisoprene: manufacturer is Hubei Xinyuhong Biopharmaceutical Technology Co., Ltd., model number is LIR-30K;

[0095] Cyclohexyl methacrylate;

[0096] Benzyl alcohol;

[0097] (2) preparing aqueous phase solution and oil phase solution;

[0098] The preparation process of the aqueous phase solution is as follows: first, pectin is uniformly dispersed in water to obtain a pectin dispersion, a hydrochloric acid solution is used to adjust the pH value of the pectin dispersion to 1, and then the pectin dispersion with the adjusted pH value is heated and stirred at 85° C. for 60 minutes, polyacrylamide, polyvinyl alcohol, PA6, and formic acid are added thereto and mixed evenly, and then heated at 95° C. for 35 minutes to obtain an aqueous phase solution; wherein the mass ratio of polyacrylamide to PA6 is 4.5:0.07, the mass ratio of polyvinyl alcohol to PA6 is 4.5:0.07, the mass ratio of pectin to PA6 is 3:0.07, and the mass ratio of water, PA6, and formic acid is 94:0.15:0.7;

[0099] The preparation process of the oil phase solution is as follows: liquid polyisoprene and cyclohexyl methacrylate are dissolved in benzyl alcohol to obtain the oil phase solution; wherein the mass ratio of the liquid polyisoprene to the benzyl alcohol is 1:32.5, and the mass ratio of the liquid polyisoprene to the cyclohexyl methacrylate is 7:1;

[0100] (3) Preparation of high tensile PA6-based hydrogel composites;

[0101] The oil phase solution and the water phase solution with a mass ratio of 4.5:5 were mixed at 105°C for 35 minutes, first frozen at -70°C, and then freeze-dried at a vacuum degree of 2Pa for 49 hours to obtain a high-stretch PA6-based hydrogel composite material.

[0102] The final high-tensile PA6-based hydrogel composite material has an elongation at break of 2748%, a tensile strength of 4 MPa, and an elastic modulus of 1.18 kPa.

[0103] Example 4

[0104] A method for preparing a high-stretch PA6-based hydrogel composite material, the specific steps are as follows:

[0105] (1) Preparation of raw materials;

[0106] Pectin: CAS number is 9000-69-5;

[0107] water;

[0108] Hydrochloric acid solution: concentration is 0.06mol / L, solvent is water;

[0109] Polyacrylamide: The manufacturer is Henan Zhengjie Environmental Protection Technology Co., Ltd., with a cationic ion degree of 20~55% and a molecular weight of 8~12 million;

[0110] Polyvinyl alcohol: CAS number is 9002-89-5;

[0111] PA6: CAS number is 25038-54-4;

[0112] Formic acid;

[0113] Liquid polyisoprene: manufacturer is Jinan Xiangfa Chemical Technology Co., Ltd., model is LIR-30K;

[0114] Cyclohexyl methacrylate;

[0115] Benzyl alcohol;

[0116] (2) preparing aqueous phase solution and oil phase solution;

[0117] The preparation process of the aqueous phase solution is as follows: first, pectin is uniformly dispersed in water to obtain a pectin dispersion, a hydrochloric acid solution is used to adjust the pH value of the pectin dispersion to 1, and then the pectin dispersion with the adjusted pH value is heated and stirred at 85° C. for 60 minutes, polyacrylamide, polyvinyl alcohol, PA6, and formic acid are added thereto and mixed evenly, and then heated at 95° C. for 30 minutes to obtain an aqueous phase solution; wherein the mass ratio of polyacrylamide to PA6 is 5:0.1, the mass ratio of polyvinyl alcohol to PA6 is 5:0.1, the mass ratio of pectin to PA6 is 3:0.1, and the mass ratio of water, PA6, and formic acid is 94:0.2:0.8;

[0118] The preparation process of the oil phase solution is as follows: liquid polyisoprene and cyclohexyl methacrylate are dissolved in benzyl alcohol to obtain the oil phase solution; wherein the mass ratio of the liquid polyisoprene to the benzyl alcohol is 1:35, and the mass ratio of the liquid polyisoprene to the cyclohexyl methacrylate is 9:1;

[0119] (3) Preparation of high tensile PA6-based hydrogel composites;

[0120] The oil phase solution and the water phase solution with a mass ratio of 4:5 were mixed at 100°C for 30 minutes, first frozen at -70°C, and then freeze-dried at a vacuum degree of 2Pa for 48 hours to obtain a high-stretch PA6-based hydrogel composite material.

[0121] The final high-tensile PA6-based hydrogel composite material has an elongation at break of 2760%, a tensile strength of 3.9 MPa, and an elastic modulus of 1.16 kPa.

Claims

1. A method for preparing a high tensile PA6-based hydrogel composite material, characterized in that: After preparing an aqueous phase solution containing PA6, polyvinyl alcohol, polyacrylamide, pectin, formic acid and water and an oil phase solution containing liquid polyisoprene, benzyl alcohol and cyclohexyl methacrylate, the aqueous phase solution and the oil phase solution are mixed at 100-110° C. for 30-40 minutes, and then freeze-dried to obtain a high-stretch PA6-based hydrogel composite material; The mass ratio of polyvinyl alcohol to PA6 is 4-5:0.05-0.1; The mass ratio of polyacrylamide to PA6 is 4-5:0.05-0.1; The mass ratio of pectin to PA6 is 3:0.05-0.1, and the mass ratio of water, PA6, and formic acid is 94:0.1-0.2:0.5-0.8; The mass ratio of liquid polyisoprene to benzyl alcohol is 1:30-35; The mass ratio of liquid polyisoprene to cyclohexyl methacrylate is 8 to 9:1; The mass ratio of the oil phase solution to the water phase solution is 4-5:

5.

2. The method for preparing a high tensile PA6-based hydrogel composite material according to claim 1, characterized in that: The freeze-drying process is: first freeze at a temperature of -70°C, and then freeze-dry at a vacuum degree of 2Pa for 48 to 50 hours.

3. A high-stretch PA6-based hydrogel composite material prepared by the method for preparing a high-stretch PA6-based hydrogel composite material as claimed in claim 1 or 2, characterized in that: The high tensile PA6-based hydrogel composite material has an elongation at break of 2629-2870%, a tensile strength of 3.8-4.2 MPa, and an elastic modulus of 1.01-1.36 kPa.

Citation Information

Patent Citations

  • High-strength and high-tensile double-network physical cross-linking hydrogel and preparation method therefor

    CN105175755A

  • High-tensile adhesive sodium alginate / polyacrylamide / tannic acid hydrogel as well as preparation method and application thereof

    CN117843995A

  • Hydrogel composite material and preparation method and application thereof

    CN112608495A

  • Hydrogel and method for producing the same

    JP2017179328A